2010
DOI: 10.1590/s1516-35982010000900022
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento ingestivo de vacas em lactação e de ovinos alimentados com dietas contendo palma forrageira

Abstract: Foram realizados dois experimentos, o primeiro com o objetivo de avaliar o efeito da substituição do feno de capim-elefante por palma forrageira e o segundo para avaliar o efeito da substituição total do milho, e parcial da soja, por palma e ureia sobre o comportamento ingestivo de ovinos e de vacas em lactação, respectivamente. No experimento 1, foram utilizados cinco ovinos machos, não-castrados, sem raça definida, com peso médio de 25,8 kg, distribuídos em quadrado latino 5 x 5. No experimento 2, foram util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
(18 reference statements)
3
2
0
3
Order By: Relevance
“…This higher efficiency observed in animals fed forage cactus silage is probably due to the absence of differences in feeding time between treatments and the higher dry matter intake observed in animals fed this silage, allowing them to consume more food per unit of time. This result is in accordance with that observed by Bispo et al (2010), who observed an increase in feeding efficiency when using forage cactus replacing elephant grass hay in sheep diet.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This higher efficiency observed in animals fed forage cactus silage is probably due to the absence of differences in feeding time between treatments and the higher dry matter intake observed in animals fed this silage, allowing them to consume more food per unit of time. This result is in accordance with that observed by Bispo et al (2010), who observed an increase in feeding efficiency when using forage cactus replacing elephant grass hay in sheep diet.…”
Section: Resultssupporting
confidence: 93%
“…Due to the high amount of water in forage cactus, the animals that fed this silage had part of their water needs already met, reducing the search for water in the drinking troughs. Bispo et al (2010), Barbosa et al (2012), andCosta et al (2012) also observed similar results.…”
Section: Resultssupporting
confidence: 72%
“…Cactus forage is an excellent source of NFC, important source of energy for ruminants (Ferreira, Silva, Bispo, & Azevedo, 2009). The results of the present behavioral research corroborate with Bispo et al (2010), who reported an increase in DM intake by sheep when associated with cactus fiber sources, especially hay.…”
Section: Resultssupporting
confidence: 89%
“…NFC levels in diets increased as they rapidly degraded the rumen, disappearing rapidly, increasing energy supply and favoring microbial growth and, consequently, digestion (Bispo et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Miranda et al (1999) worked with Holstein x Zebu crossbred heifers fed diets based on sugar cane, using different levels of NPN and probiotics and found no difference in feeding time. Bispo et al (2010) worked with lactating cows in which they added palm and urea in the diets and observed no change in feeding and idle time, probably due to the fact that consumption of DM and NDF was not influenced by the inclusion of these foods and the concentration of NDF in the diets are similar. Despite the changes in feeding and idle times, the DM and NDF intakes (Table 5) were similar (P > 0.05) between the different levels of substitution of soybean brain by urea, suggesting an adaptation of the ingestive behavior of the cows.…”
Section: Resultsmentioning
confidence: 99%